2008
DOI: 10.3899/jrheum.080268
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibody-Associated Chorea

Abstract: aPL-associated chorea occurs most often in women and severity is mild to moderate. Clinical expression of chorea does not differ between those with and without SLE. Anticoagulation should be reserved for thrombosis treatment and not simply for chorea in the presence of aPL, as 2 patients died of bleeding. The absence of IgM aCL in patients with APS supports prior evidence that IgG aCL and lupus anticoagulant may be the more clinically relevant antibodies for thrombosis. However, IgM aCL may be important in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 20 publications
2
50
0
3
Order By: Relevance
“…Symptomatic therapy with dopamine antagonists is usually effective and glucocorticoids in combination with immunosuppressive agents (azathioprine, cyclophosphamide) may be used to control NPSLE disease activity. Antiplatelet and/or anticoagulation therapy is administered in antiphospholipid-positive patients, especially when other antiphospholipid/APS-related manifestations are present 36 61 62…”
Section: Resultsmentioning
confidence: 99%
“…Symptomatic therapy with dopamine antagonists is usually effective and glucocorticoids in combination with immunosuppressive agents (azathioprine, cyclophosphamide) may be used to control NPSLE disease activity. Antiplatelet and/or anticoagulation therapy is administered in antiphospholipid-positive patients, especially when other antiphospholipid/APS-related manifestations are present 36 61 62…”
Section: Resultsmentioning
confidence: 99%
“…We therefore inferred that chorea did not result from a hypercoagulable state and concluded that anticoagulation should be reserved for treating thrombosis, but not chorea. 27 The infrequency of neural-specific antibody detection in patients with idiopathic autoimmune chorea (5 of 21 patients) leads us to conclude that pertinent autoantibody markers remain to be discovered.…”
mentioning
confidence: 99%
“…[21][22][23] In the literature there are no clinical studies on the use of IVIG in children with aPL-related chorea. On the other hand, there are data on the use of IVIG treatment in SC.…”
mentioning
confidence: 99%